Systematic literature review on infographic adaptation and acceptance factors in facilitating teaching and learning across higher education and medical fields - Ahmad, Ahmad Khairul Azizi; Ramlie, Mohd Khairulnizam; Abdul Aziz, Mohd Nasiruddin; Rahaman, Ashraf Abdul; Firdaus Muhammad, Intan Nor (Universiti Teknologi MARA, Perak, 2025)
Infographics are visual representations of information designed for rapid understanding at a glance. As powerful stimulators of visual communication, infographics have gained significant popularity among educators in higher education and medical fields. The creation of engaging teaching and learning materials has become increasingly critical, yet systematic reviews focused on infographic acceptance and adaptation remain scarce. This study conducts a comprehensive systematic literature review adhering to the ROSES protocol (RepOrting standards for Systematic Evidence Syntheses), selecting studies from Scopus, Science Direct, and Google Scholar. A total of 19 empirical studies were included in the final synthesis. A thematic analysis revealed four main themes: (1) Clarity and Efficiency in Information Delivery; (2) Enhancing Comprehensibility; (3) Development of Visual Literacy Competencies; and (4) Promotion of Active Teaching and Learning Practices. The findings highlight the essential role of infographics in enhancing comprehension, promoting engagement, and facilitating the rapid transfer of knowledge, particularly in health-related education. This paper contributes meaningful insights into the role of infographics in teaching and learning while identifying key areas for future research and curriculum development.